Madura, Clay County - Cox, Joshua M. (Kansas State University, The Chapman Center for Rural Studies, 2012)
The story of one missionary’s journey around the world, eventually ending in Kansas and the founding of a town, incorporates biographies, census data, genealogical research, photographs, plat maps, and personal interviews.
Joshua M. Cox, “Madura, Clay County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/97.
Keywords: Clay County; Madura; Kansa Indians; Republic Township; Wakefield; William Payne